Highly soluble phenylethynyl-endcapped imide oligomers derived from thioetherdiphthalic anhydride isomers. (April 2017) - Sun, Lu; Wang, Wei; Chen, Guofei; Fang, Xingzhong
Novel imide oligomers (calculated molecular weights: 1250–5000 g mol −1 ) based on the mixture of thioetherdiphthalic anhydride isomers ( m -TDPA) with 2-phenyl-4, 4′-diaminodiphenyl ether ( p -ODA) in the presence of 4-phenylethynylphthalic anhydride (PEPA) as reactive endcapping agent were prepared. Then pyromellitic dianhydride (PMDA) was introduced to the polymerization of m -TDPA/ p -ODA (mole m -TDPA :molePMDA = 1:1). The effect of molecular weights and polymer chemical structures of the aromatic oligomers on their processability and solubility as well as the thermal and mechanical properties of the thermal-cured polyimides (PIs) was systematically investigated. All the oligomers showed good solubility (more than 30 wt%) in N -methyl-2-pyrrolidone and very low melt viscosities. The minimum melt viscosities of Oligo-5 was 61.5 Pa s at 321°C. The melt viscosity of the oligomers increased with the increase of molecular weight. After thermally curing at 370°C for 1 h, the thermoset PIs exhibited good thermal properties. The glass transition temperatures of oligomers measured by differential scanning calorimetry were in the range of 264–337°C, and the temperature of 5% weight loss was higher than 505°C. The cured films also demonstrated good mechanical properties with tensile strength and modulus greater than 52 MPa and 2.9 GPa, respectively.